2012
DOI: 10.1590/s1517-83822012000400039
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Agro-industrial Wastes for the Simultaneous Production of Amylase and Xylanase by Thermophilic Actinomycetes

Abstract: Agro-industrial wastes such as sugarcane bagasse, wheat bran, rice bran, corn cob and wheat straw are cheapest and abundantly available natural carbon sources. The present study was aimed to production of amylase and xylanase simultaneously using agro-industrial waste as the sole carbon source. Seven thermophilic strains of actinomycete were isolated from the mushroom compost. Among of these, strain designated MSC702 having high potential to utilize agro-industrial wastes for the production of amylase and xyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…When the incubation period was increased, there was a decrease in amylase production. Singh et al, (2012) also reported that Streptomyces sp. MSC702 produced maximum quantity of amylase after an incubation period of 48 h. According to Gupta et al, (2008), the decrease in activity at the later phase of growth probably was because of catabolite repression by glucose which was released from starch hydrolysis.…”
Section: Effect Of Metal Ions On Partially Purified Amylase Activitymentioning
confidence: 92%
“…When the incubation period was increased, there was a decrease in amylase production. Singh et al, (2012) also reported that Streptomyces sp. MSC702 produced maximum quantity of amylase after an incubation period of 48 h. According to Gupta et al, (2008), the decrease in activity at the later phase of growth probably was because of catabolite repression by glucose which was released from starch hydrolysis.…”
Section: Effect Of Metal Ions On Partially Purified Amylase Activitymentioning
confidence: 92%
“…showed potential for enzyme production using different agroindustrial residues. It produced maximum xylanases on a medium containing rice bran as a substrate (Singh et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…using molecular methods including 16S rRNA sequencing. Singh et al (2012) also identified a novel Streptomyces strain using morphological and molecular characterization including the 16S rRNA gene sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum amylase activity (373.89 IU/ml) was obtained with rice bran at pH 7.0 after incubation of 48 hours by Streptomyces MSC702 in submerged fermentation (Singh et al, 2012). It was investigated that productive medium supplemented with 2% potato starchy waste as a low price substrate could be more favorable than basal medium containing 1% starch for amylases production in submerged fermentation, as it increased α, β and γ amylase activity by 1.98, 7.69 and 12-fold than that produced in basal medium (AbdElhalem et al, 2015).…”
Section: Production Of Amylase Using Agro Wastesmentioning
confidence: 97%